Recognizing the Mallee: Reading Groups and the Making of Literary Knowledge in Regional Australia - Magner, Brigid; Potter, Emily (Mémoires du livre / Studies in Book Culture, 2021)
Drawing on fieldwork in the Victorian Mallee region of Australia, this article explores the ways in which reading groups can elicit rich information about the relationship between literature, reading, and place. The study found that book group participants “recognized” the Mallee in the texts under discussion and engaged in their own forms of place knowledge and “history‑telling” in response, making corrections to, and even rejecting, literary representations of their area. We argue that the resources for enhancing literary infrastructure exist, both in the broad history and diversity of Mallee writing, and in the social infrastructure of the Mallee. Readers’ knowledge, captured through book‑related discussion in community spaces, offers the potential for enhancing existing literary resources in rural and remote regions.